Impact of Preoperative Nutritional Status on Wound Healing and Complication Rates in Elective General Surgeries - Rohma Afzal ,; Haseeb Ahmad,; Uswa Khalid,; Zoha Zulfiqar,; Kalsoom Bibi, (Pakistan Journal of Medical & Health Sciences, 2025)
Background: Nutritional status is a critical determinant of postoperative recovery, influencing immune function, collagen synthesis, and tissue repair. Malnutrition remains underdiagnosed in surgical populations, particularly in low- and middle-income countries, contributing to avoidable postoperative complications. This study evaluates the impact of preoperative nutritional status on wound healing and postoperative outcomes in elective general surgical patients. Objective: To assess the association between preoperative nutritional status and postoperative wound healing, complication rates, and hospital stay in patients undergoing elective general surgeries. Methods: A prospective observational study was conducted from February 2023 to June 2024 at Sheikh Zayed Hospital and Fatima Memorial Hospital, Lahore. A total of 80 patients undergoing elective general surgeries were enrolled through consecutive sampling. Nutritional assessment included BMI, serum albumin, hemoglobin, TLC, and MUST scoring. Patients were categorized as well-nourished or malnourished. Postoperative outcomes primary wound healing, delayed healing, surgical site infection (SSI), seroma, hematoma, and wound dehiscence were recorded over a 30-day follow-up. Data were analyzed using SPSS 26, with p < 0.05 considered significant. Results: Malnutrition was identified in 35% of patients. Malnourished patients showed significantly higher rates of delayed healing (42.8% vs. 13.4%), SSI (32.1% vs. 5.7%), and wound dehiscence (10.7% vs. 1.9%). Mean hospital stay was markedly longer in malnourished patients (8.2 ± 2.9 days) compared to well-nourished patients (4.9 ± 1.6 days). Logistic regression identified serum albumin <3.5 g/dL and hemoglobin <11 g/dL as independent predictors of complications. Conclusion: Poor preoperative nutritional status significantly increases wound-related morbidity and prolongs postoperative recovery. Routine nutritional screening and timely optimization should be integrated into preoperative surgical care.